The effectiveness of Sustained Natural Apophyseal Glide on Flexion Rotation Test, pain intensity, and functionality in subjects with Cervicogenic Headache: A Systematic Review of Randomized Trials - Ricardo Cardoso; Adérito Seixas; Sandra Rodrigues; Isabel Moreira-Silva; Nuno Ventura; Joana Azevedo; Filippo Monsignori (Archives of Physiotherapy, 2022)
Abstract Objective To determine the effect of sustained natural apophyseal glide (SNAG) on Flexion Rotation Test, pain intensity, and functionality in subjects with Cervicogenic Headache (CH). Methods The research was conducted on five computerized databases PubMed/Medline, Web of Science, PEDro, Lilacs, and Cochrane Library (CENTRAL), using the keywords combination: (sustained natural apophyseal glide OR SNAG OR joint mobilization OR Mulligan) AND (cervicogenic headache) according to PRISMA guidelines. The methodological quality of the included studies was analyzed using the Physiotherapy Evidence Database (PEDro) scale. Results Eight articles fulfilled the eligibility criteria and were included in the review. The selected studies had a methodological quality of 6.6/10 on the PEDro scale and included a total of 357 participants. The SNAG significantly improved pain, Flexion Rotation Test and reduced functional symptoms. Conclusion The available evidence suggests that SNAG may be a relevant intervention for CH.